Perancangan Sistem Informasi Percetakan Berbasis Web pada Citra Grafika - Saragih, Alberta Vikasari; Roni J. Simamora; Rimbun Siringoringo; Jamaluddin, Jamaluddin (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
This study aims to design a web-based printing information system for Citra Grafika, which previously managed orders and generated reports manually. The manual system caused inefficiency, difficulty in searching for data, delays in report preparation, and a high risk of data loss. This study used observation, interviews, and literature review methods to collect system requirements. The system was developed using PHP and MySQL with features for online ordering, product management, customer data management, order status tracking, and report generation. The results of the study show that this system can improve operational efficiency, minimizing recording errors, and improving the quality of customer service. This web-based information system is expected to support decision making and increase Citra Grafika's competitiveness in the digital era.